A Geopolymer as a Low-Carbon Structural Solution for Disaster Risk Mitigation: A Systematic Review Based on the IPCC Perspective - Kurniasari, Paramita Tri; Hargono , Arief; Kristianto, Sonny; Prana Iswara , Aditya (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2025)
The climate crisis and increasing intensity of natural disasters demand an integrated solution encompassing both structural and social dimensions. The construction industry, particularly the use of Portland cement (OPC), accounts for approximately 7–8% of global carbon emissions, and the vulnerability of infrastructure to disasters further elevates risks for communities. This study addresses a gap in the literature by integrating low-carbon material innovations, specifically geopolymer concrete, with community-based preparedness strategies within the framework of disaster risk mitigation and IPCC climate policy. A systematic literature review was conducted on 35 selected publications from Scopus, ScienceDirect, Google Scholar, and IPCC AR6 reports. Findings indicate that geopolymer concrete can reduce carbon emissions by up to 97%, exhibits high resistance to heat, earthquakes, and corrosive environments, and is suitable for infrastructure in disaster-prone areas. Social strategies such as education, evacuation drills, and strengthening local institutions have proven effective in enhancing community resilience. This study proposes a “dual-resilience” framework that combines structural strength with social capacity, which is relevant for mainstreaming in sustainable development policies in Indonesia. Keywords: Geopolymer, Carbon Emissions, Community Preparedness, Disaster Mitigation, IPCC, Low Carbon Concrete